Facile One-Pot Access to α-Diazo-β-ketosulfones from Sulfonyl Chlorides and α-Haloketones - Dar’in, Dmitry; Kantin, Grigory; Bakulina, Olga; Krasavin, Mikhail (Synthesis, 2020)
A convenient one-pot approach to the preparation of α-diazo-β-ketosulfones from sulfonyl chlorides is described. It involves the conversion of the sulfonyl chloride to sodium sulfinate, alkylation of the latter with α-haloketones followed by diazo transfer using the ‘sulfonyl-azide-free’ (‘SAFE’) protocol in aqueous medium. The simple and expedient method relies on readily available starting materials and provides facile access to a wide variety of valuable diazo reagents for organic synthesis.
Keywords: aliphatic diazo compounds; diazo ketosulfones; diazo transfer; α-haloketones; Rh(II)-catalyzed cyclization; pyrazole synthesis